P359 A novel phase 1 trial design to evaluate safety, tolerability, pharmacokinetics, and pharmacodynamics of TOP1288, a narrow spectrum kinase inhibitor, delivered topically to the colon via oral administration. (16th January 2018) - Rowley, A; Taylor, M; Duggal, A; Foster, M; Sirohi, S; Solanke, Y; Walshe, C; Fyfe, M; Webber, S; Travis, S
Abstract: Background: TOP1288 is a topically acting, narrow spectrum kinase inhibitor that selectively targets key kinases (p38apha, Src family kinases, and Syk) involved in inflammatory signalling in cells of the innate and adaptive immune systems. TOP1288 has minimal systemic absorption, is free from systemic or local toxicities and has potential to provide a safe and efficacious, chronic dosing treatment for inflammatory bowel disease (IBD) as demonstrated by a prior study with a rectal formulation. 1, 2 Combining an innovative trial design with bespoke assays of target engagement and immune responses in serial colon biopsies, this phase 1 study evaluates the safety, tolerability, and local pharmacokinetics/pharmacodynamics of orally administered TOP1288. Methods: Single and multiple doses of TOP1288, formulated as a granule for oral suspension, were administered to healthy male volunteers ( n = 36) in a phase 1, randomised, double blind, placebo controlled study. Safety parameters were assessed and serial blood samples taken for PK analysis. Subjects in Cohorts 1 and 2 received a single dose (200 mg BID or 1 g BID) ( n = 7) of TOP1288 or matching placebo ( n = 3). Cohort 3 subjects received multiple oral doses of TOP1288 (200 mg BID, days 1–3, then 600 mg BID days 4–7) ( n = 10) or placebo (day 1 through day 7) ( n = 6). To confirm delivery of solubilised TOP1288 to the colon, multiple biopsies were obtained via serial sigmoidoscopies in the same patients up to 36 h after last dose for measurement of TOP1288 tissue drug concentrations and temporal target engagement/pharmacodynamic responses. Results: TOP1288 was well tolerated with no safety concerns. Plasma concentrations were low (<0.4ng/ml) whereas, in all subjects, TOP1288 was readily quantified at pharmacologically relevant concentrations (cohort mean range 124–445 ng TOP1288/mg protein) in biopsies taken from multiple areas in the descending colon, even those taken 36 h after last dose. Stimulated phosphorylated Lck, a marker of target engagement assessed in isolated lamina propria mononuclear cells (LPMCs), decreased in a dose dependent manner with maximal inhibition at 1 g BID (single dose) and 600 mg BID (multiple dose). IL 8 production from LPMCs, a localised innate immune response to biopsy excision (measured in Cohort 3 only) was similarly inhibited up to 24 h after last dose in subjects receiving TOP1288 (600 mg BID). Conclusions: TOP1288 is safe and well tolerated with low systemic exposure following oral dosing. Sustained, pharmacologically relevant TOP1288 concentrations are delivered to the colon as measured by direct quantification in tissue samples and biomarker assays. TOP1288 may be a promising new oral therapy for the treatment of IBD. References: 1. Rowley A et al. First-in-human randomized double-blind placebo-controlled clinical trial of a novel narrow spectrum kinase inhibitor. Gastroenterology, 2016;150:S776. http://www.gastrojournal.org/article/S0016-5085(16)32631-2/abstract . 2. Taylor M, et al. A first clinical trial of a novel narrow spectrum kinase inhibitor TOP1288 in patients with ulcerative colitis. J Crohn's Colitis, 2017;11:S429–30. https://doi.org/10.1093/ecco-jcc/jjx002.808